Modeling of New Single-Phase High Voltage Power Supply for Industrial Microwave Generators for N=2 Magnetrons - Ali Bouzit; Mohammed Chraygane; Naama El Ghazal; Mohammed Ferfra; M Ferfra; M Bassoui (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In this paper, we propose to study the modeling and the simulation, using the EMTP code, of the operation in nominal mode of a new high voltage power device, based on the same use principle of an only transformer with shunts, but this time for several magnetrons. This modeling can lead to the determination of the construction parameters of the new transformer, to ensure the correct operation in nominal mode of the new power supply, while respecting the control criterion of the current in each magnetron. The knowledge of these parameters (size of the magnetic circuit, the magnetic quality, the air gap, the size of the shunt and the number of turns, etc .....), determines the cost of the dimensioned transformer for its realization. In the following, we will treat all possible states for operation of this new power supply with two magnetrons (Power supply for two magnetrons: case of two magnetrons in service, case of one magnetron in service and one magnetron in failure, case of tow magnetrons in failure). This provides relative to the current device gains of space, volume, cost of implementation and maintenance.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5686